C74 ESCALATION AND DE–ESCALATION OF MECHANICAL CIRCULATORY SUPPORT IN PATIENT WITH CARDIOGENIC SHOCK DUE TO ELECTRICAL STORM. (18th May 2022) - Sorini Dini, C; Maccherini, M; Bernazzali, S; Righini, F; Biagioni, G; Valente, S
Abstract: : We describe a case of a 63 year–old man with familiar dilated cardiomyopathy, with severe left ventricle dysfunction (EF 20%) and severe mitral regurgitation.A progressive worsening of functional status was detected (peak VO2 11 ml/kg/min, NYHA III) with some episodes of VT interrupted by bicameral ICD, for which the patient was referred to our center and included in the heart transplant (HT) list. In the following months sustained VT with hemodynamic impact were recorded, with consequent worsening in class INTERMACS 2. The patient underwent to endocardial and epicardial VT ablation, complicated with electrical storm with deterioration towards cardiogenic shock (INTERMACS 1), requiring vaso–inotropic drugs, mechanical ventilation and femoro–femoral VA–ECMO.The patient was centralized in our ICCU, where he maintained a adequate MAP, SvcO2 50% and active diuresis but at echocardiography left ventricle appeared dilated with high filling pressure, X–ray and pulmonary ultrasonography showed congestion, lactate value rapidly increased (5 mmol/mol), renal and hepatic function worsened (creat 2 mg/dl, bil 2.8 mg/dl). After multidisciplinary discussion an escalation of mechanical circulatory support (MCS) was performed, changing ECMO configuration: an arterial cannula was positioned in the right axillary artery and venting cannula positioned in the apex of the left ventricle. The hemodynamic and respiratory parameters quickly improved, the right pulmonary catheterization showed good pulmonary resistence, organ perfusion improved and neurological status was intact, therefore the patient was inserted in emergency list for HT. After few days a de–escalation of MCS was performed, removing venous cannula and oxygenator, changing the circuit in para–corporeal left ventricle mid–term support as bridge to transplantation. The patient maintained conscious, in spontaneous breathing, able to perform physiotherapy and spontaneous nutrition. The de–escalation of MCS allowed to reduce potential complications of MCS and achieve the HT intervention in a better general and functional condition. After 36 days the patient underwent HT with positive outcome. Conclusion: MCS are device that require a continuous re–assessment a re–modulation to ensure in the early stages the optimization of haemodynamic support, perfusion of vital organs and unloading of the Vsx and in the following stages an adjustment to long–term strategies (bridge to recovery, bridge to VAD, bridge to heart transplantation).